2022
DOI: 10.3390/nu14214524
|View full text |Cite
|
Sign up to set email alerts
|

Federal Food Assistance Program Participation during the COVID-19 Pandemic: Participant Perspectives and Reasons for Discontinuing

Abstract: This study aims to describe reasons for discontinuing participation and experiences participating in the Supplemental Nutrition Assistance Program (SNAP) and the Special Supplemental Nutrition Assistance Program for Women, Infants, and Children (WIC) during the COVID-19 pandemic. We analyzed data from a cross-sectional online survey distributed to a national sample, restricted to (1) households that discontinued participating in SNAP (n = 146) or WIC (n = 149) during the pandemic and (2) households that partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Despite the implementation of program modifications during this time, benefit redemption challenges were common. Consistent with the results of previous research, many participants had difficulty finding WIC-approved items in stores due to a lack of shelf labeling and low stock of WIC foods [ 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 ]. Some participants also experienced confusion when determining which brands and sizes were WIC-eligible [ 17 , 24 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Despite the implementation of program modifications during this time, benefit redemption challenges were common. Consistent with the results of previous research, many participants had difficulty finding WIC-approved items in stores due to a lack of shelf labeling and low stock of WIC foods [ 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 ]. Some participants also experienced confusion when determining which brands and sizes were WIC-eligible [ 17 , 24 ].…”
Section: Discussionsupporting
confidence: 84%
“…A large body of previous research demonstrates that WIC participants often face difficulties with in-store benefit redemption [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Several factors have been shown to contribute to these redemption challenges including a lack of accurate, consistent shelf labeling [ 10 , 11 , 17 , 18 , 19 , 20 , 21 ], low stock of WIC-approved foods [ 11 , 15 , 16 , 20 , 22 , 23 ], issues at the checkout (i.e., perceived stigma and long waiting times) [ 10 , 11 , 17 , 24 ], confusion about WIC-eligible items (i.e., brands and sizes) [ 17 , 24 ], and inconsistencies between the register and the information participants receive from the program/WIC apps, particularly following program and policy changes [ 20 , 22 , 24 ]. These challenges were exacerbated by the COVID-19 pandemic and related issues such as global grocery retail shortages and rising food and household costs [ 1 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, barriers, such as extra fees (e.g., service fee and delivery fee), challenges associated with technologies to adopt online shopping, and limitations associated with using SNAP/WIC benefits for online grocery shopping, have prohibited many of the participants who never used online grocery shopping before COVID-19 from adopting online grocery shopping during COVID-19. During the middle stage of the pandemic, although the overall amount of SNAP participants was similar to that during the initial stage, research suggested that around 30 percent of SNAP participants discontinued their benefits due to being unqualified, limitation in using the benefits online, and/or thinking the benefits not worth the efforts to apply (Melnick, Ganderats-Fuentes, and Ohri-Vachaspati 2022). That means there were quite a number of new SNAP participants during the middle stage of the pandemic and shopping behavior of these new SNAP participants may have made the overall effect of the SNAP/WIC participant variable insignificant during the middle stage of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggested that SNAP/WIC participants often have difficulty performing in-store grocery shopping due to the lack of gas money and time to travel to stores and lower mobility (Melnick, Ganderats-Fuentes, and Ohri-Vachaspati 2022). As a result, they may have a higher demand for online grocery shopping or other non-traditional food acquisition options, such as cooking with others and obtaining food from coworkers, friends and neighbors (Kaiser and Hermsen 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Still, more efforts are needed to address barriers that food assistance recipients face and to improve both digital and nutrition literacy [ 21 ]. For example, according to an online survey study assessing reasons for discontinuing participation in food assistance programs, households receiving WIC were particularly discouraged by difficulties in redeeming benefits, and SNAP participants expressed a desire for better online grocery purchasing experiences [ 74 ]. In the present study, the main obstacles to online grocery shopping were a need for more knowledge, expenses not covered by food assistance programs, and reservations about food selection.…”
Section: Discussionmentioning
confidence: 99%